Respostas
respondido por:
0
A( - 2 , 5 ) B( x , x - 7 ) dAB = 10
xa ,ya xb, yb
dAB = 10
(xa - ab)² + (ya - yb)² = d²AB
(- 2 - x)² + ( - 5 -(x - 7) )² = 10²
( - 2 - x)²+ ( - 5 - x + 7)² = 100
(-2)² - 2.(-2).x + x² + (2 - x)² = 100
4 + 4x + x² + 4 - 4x + x² = 100
2x² + 8 - 100 = 0
2x² - 92
x² = 92/2
x² = 46
x = ( + ou -) √46 B( √46 , √46 - 7) e B( - √46 , - √46 - 7 )
xa ,ya xb, yb
dAB = 10
(xa - ab)² + (ya - yb)² = d²AB
(- 2 - x)² + ( - 5 -(x - 7) )² = 10²
( - 2 - x)²+ ( - 5 - x + 7)² = 100
(-2)² - 2.(-2).x + x² + (2 - x)² = 100
4 + 4x + x² + 4 - 4x + x² = 100
2x² + 8 - 100 = 0
2x² - 92
x² = 92/2
x² = 46
x = ( + ou -) √46 B( √46 , √46 - 7) e B( - √46 , - √46 - 7 )
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás